2000
DOI: 10.1523/jneurosci.20-14-05496.2000
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin-Releasing Peptide Phase-Shifts Suprachiasmatic Nuclei Neuronal RhythmsIn Vitro

Abstract: The main mammalian circadian pacemaker is located in the suprachiasmatic nuclei (SCN) of the hypothalamus. Gastrin-releasing peptide (GRP) and its receptor (BB(2)) are synthesized by rodent SCN neurons, but the role of GRP in circadian rhythm processes is unknown. In this study, we examined the phase-resetting actions of GRP on the electrical activity rhythms of hamster and rat SCN neurons in vitro. In both rat and hamster SCN slices, GRP treatment during the day did not alter the time of peak SCN firing. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 45 publications
1
79
0
1
Order By: Relevance
“…night (Piggins and Rusak, 1993;Piggins et al, 1994Piggins et al, , 1995Albers et al, 1995;McArthur et al, 2000). It has also been shown that the phase-shifting effects of a gastrin-releasing peptide injection can be blocked by the application of the gastrin-releasing peptide antagonist [D-F5Phe6,D-Ala11]BN(6 -13)OMe (Piggins et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…night (Piggins and Rusak, 1993;Piggins et al, 1994Piggins et al, , 1995Albers et al, 1995;McArthur et al, 2000). It has also been shown that the phase-shifting effects of a gastrin-releasing peptide injection can be blocked by the application of the gastrin-releasing peptide antagonist [D-F5Phe6,D-Ala11]BN(6 -13)OMe (Piggins et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Intercellular signaling through VIP and its receptor VPAC2 is critical in maintaining the synchrony of SCN cellular oscillators and circadian function within the SCN (Aton et al 2005;Maywood et al 2006). In addition, GRP cells are retinorecipient, they communicate with cells in the shell region through GRP receptors, and they function to keep SCN neurons synchronized during entrainment (McArthur et al 2000;Aida et al 2002;Karatsoreos et al 2004;). …”
Section: Function Of Scn Subregionsmentioning
confidence: 99%
“…CalB (Bryant et al, 2000) and GRP (Aioun et al, 1998) cells receive retinal terminals and presentation of a light pulse during the night induces c-Fos in about 80% of the CalB cells (Silver et al, 1996), 78% of the GRP cells and 60% of the VIP cells (Aioun et al, 1998). It is also known that administration of GRP (McArthur et al, 2000) or coadministration of VIP, peptide histidine isoleucine and GRP (Albers et al, 1991) induce phase-dependent resetting of the SCN that resembles the lightinduced phase response curve. Finally, administration of CalB antisense blocks lightinduced phase shifts (Hamada et al, 2000).…”
Section: Colocalization Of Peptides In the Calb Subnucleusmentioning
confidence: 99%